Are resident handlings in eldercare wards associated with musculoskeletal pain and sickness absence among the workers? A prospective study based on onsite observations - Leticia Bergamin Januario; Svend Erik Mathiassen; Matthew L Stevens; Andreas Holtermann; Gunnar Bergström; Reiner Rugulies; Kristina Karstad; David M Hallman (Nordic Association of Occupational Safety and Health (NOROSH), 2021)
OBJECTIVES: We aimed to identify eldercare wards with different types of resident handling characteristics ('phenotypes') and determine the prospective association between these characteristics and musculoskeletal pain and sickness absence among workers during a one-year follow-up. METHODS: Our study was based on the DOSES cohort, including 467 workers at 103 eldercare wards. At baseline, resident handlings were assessed using onsite observations. Workers' self-reported musculoskeletal pain and sickness absence were assessed during the following year using text messages. Observations of the frequency of handlings per shift, use of assistive devices, assistance from others, and barriers (interruptions and impediments) were estimated for each worker, aggregated at ward level, and entered into a latent profile analysis, identifying ward phenotypes. We then used generalized estimating equations to determine associations between ward phenotypes, musculoskeletal pain and sickness absence. RESULTS: We identified four ward phenotypes: 'turbulent' (many handlings with devices and assistance, many barriers), 'strained' (many handlings without devices or assistance, some barriers), 'unpressured' (few handlings, yet without devices or assistance, few barriers) and 'balanced' (some handlings with devices and assistance, some barriers). Compared to workers in balanced wards, workers in turbulent wards had more days with neck-shoulder and low-back pain (LBP); and those working in strained wards had more days with LBP and higher pain intensities. CONCLUSION: We found that ward phenotypes based on resident handling characteristics were predictive of musculoskeletal pain and sickness absence over one year. This shows that organizational factors related to resident handling are important determinants of musculoskeletal health among eldercare workers.